2015
DOI: 10.1016/j.pharep.2015.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Icariin regulates PRMT/ADMA/DDAH pathway to improve endothelial function

Abstract: The present results suggest that icariin regulates PRMT/ADMA/DDAH pathway to improve endothelial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The TD and icariin group were fed same diet as control group but with the addition of tetramethylthiuram disulfide (thiram) 50 mg/kg of feed from days 3 to 7 posthatch to induce TD. After induction of TD on day 8, the icariin group was separated and fed with standard normal diet with the addition of 10 mg/kg/day icariin ( Xiao et al, 2015 ) through drinking water until the end of experiment, while TD group was given standard normal diet without adding thiram, just like control group.…”
Section: Methodsmentioning
confidence: 99%
“…The TD and icariin group were fed same diet as control group but with the addition of tetramethylthiuram disulfide (thiram) 50 mg/kg of feed from days 3 to 7 posthatch to induce TD. After induction of TD on day 8, the icariin group was separated and fed with standard normal diet with the addition of 10 mg/kg/day icariin ( Xiao et al, 2015 ) through drinking water until the end of experiment, while TD group was given standard normal diet without adding thiram, just like control group.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have suggested that Icariin attenuated the development of atherosclerosis in several animal models, including ApoE -/- mice ( Xiao et al, 2015 , 2017 ; Wang et al, 2016 ), rats ( Hu et al, 2015b ), and rabbits ( Zhang et al, 2013 ). The atheroprotective mechanisms of Icariin are exerted through anti-oxidative, anti-inflammatory, anti-thrombotic, and lipid-modulatory effects.…”
Section: Anti-atherosclerotic Effects Of Icariinmentioning
confidence: 99%
“…Furthermore, Icariin also increase eNOS activity by blocking eNOS uncoupling through decreasing the level of ROS and asymmetric dimethylarginine (ADMA) by increasing the level of dimethylarginine dimethylaminohydrolase (DDAH) in ApoE -/- mice. The resulted effect is increasing endothelium-dependent vasorelaxation ( Xiao et al, 2015 ). Recent evidence has also suggested that Icariin reduces oxLDL-induced monocyte adhesion to endothelial cells, the initiating event in atherosclerosis.…”
Section: Anti-atherosclerotic Effects Of Icariinmentioning
confidence: 99%
“…For one thing, DDAH activity is negatively regulated by lysophosphatidylcholine, homocysteine, and oxidized low‐density lipoprotein. For another thing, DDAH is positively modulated by antioxidant such as icariin, all‐trans‐Retinoic acid, pyrrolidine dithiocarbamate, and xanthone . Additional investigations reports that elevated productions of ROS reduce the level of bioactive NO .…”
Section: Discussionmentioning
confidence: 99%